Gambaran Pelaksanaan 10T Pada Antenatal Care (ANC) Terpadu di Wilayah Kerja Puskesmas Sukowono Kabupaten Jember - Putri, Erin Verensia; Herawati, Yennike Tri; Witcahyo, Eri (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Antenatal care (ANC) service program is one of the efforts to reduce maternal mortality. However, as per the Jember District Health Office report in 2021, the coverage of K1 was 103.64% and K4 was 58.67%, which is still below the target of 100%. The low level of public knowledge regarding ANC visits and incomplete counseling provided by midwives to maternal according to the current guidelines were the main reasons for the failure to achieve the K4 target for Integrated ANC visits and the occurrence of MMR in the working area of Sukowono Health Center. Aims: The purpose of this study is to describe the implementation of Integrated Antenatal Care (ANC) in Sukowono Health Center's working area, Jember Regency. Methods: A descriptive study was conducted in the working area of Sukowono Public Health Center, Jember Regency, focusing on 28 health workers who carried out Integrated ANC. The study recruited a total of 28 midwives through total sampling. The data collection techniques used in this research were interviews and documentation studies. Results: The research and documentation study carried out in the Working Area of Sukowono Public Health Center, Jember Regency, revealed that only two midwives (7.2%) conducted frequent speech interviews (counseling) and mental health assessments in the implementation of 10T in integrated ANC. However, all midwives regularly carried out 10T on K4 in integrated ANC, and only one midwife (3.6%) conducted case management frequently on K6 in Integrated ANC in the Work Area of the Sukowono Health Center, Jember Regency. Conclusion: The implementation of the 10T program in the Integrated ANC of the Sukowono Health Center, Jember Regency, has been evaluated and categorized. The implementation of 10T in K1 has been included in the unfavorable category, while the implementation in K4 has been categorized as good. However, the implementation of 10T in K6 has been included in the unfavorable category. It is crucial for counseling and case management to be carried out properly to ensure the health of mothers and prevent maternal mortality.